Loop-mediated isothermal amplification (LAMP) assay coupled with gold nanoparticles for colorimetric detection of Trichoderma spp. in Agaricus bisporus cultivation substrates - Mila Djisalov; Ljiljana Janjušević; Vincent Léguillier; Ljiljana Šašić Zorić; Carole Farre; Jamila Anba-Mondoloni; Jasmina Vidic; Ivana Gadjanski (Scientific Reports, 2024)
Abstract One of the significant challenges in organic cultivation of edible mushrooms is the control of invasive Trichoderma species that can hinder the mushroom production and lead to economic losses. Here, we present a novel loop-mediated isothermal amplification (LAMP) assay coupled with gold nanoparticles (AuNPs) for rapid colorimetric detection of Trichoderma spp. The specificity of LAMP primers designed on the tef1 gene was validated in silico and through gel-electrophoresis on Trichoderma harzianum and non-target soil-borne fungal and bacterial strains. LAMP amplification of genomic DNA templates was performed at 65 °C for only 30 min. The results were rapidly visualized in a microplate format within less than 5 min. The assay is based on salt-induced aggregation of AuNPs that is being prevented by the amplicons produced in case of positive LAMP reaction. As the solution color changes from red to violet upon nanoparticle aggregation can be observed with the naked eye, the developed LAMP-AuNPs assay can be easily operated to provide a simple initial screening for the rapid detection of Trichoderma in button mushroom cultivation substrate.